Implementasi Perpustakaan Digital di Institut Teknologi Bandung - Nanan Hasanah (Jurnal Pustakawan Indonesia, 2006)
In order to develop sciences owned by ITB, the ITB Digital Library was developed. The ITB Library programs related to the intellectual property covered and considered some important items, such as the content or library’s collection, atmosphere and attitude developed. Knowledge covered in the ITB Digital Library was categorized according to the kinds of information. The categories chosen are: the Student Last Project (Skripsi), that is the student’s last project for undergraduate level; Thesis, that is the last project of the graduate students;Dissertation, that is the student’s last project of the Ph.D. level; E-clipping, that is the electronic newspaper article; Proceeding, that is the papers from seminar, workshop, scientific meeting held in ITB, and the products of the civitas academica;Research Report from any research groups in ITB; Grey Literature, that is the unpublished documents of the ITB civitas academica, such as inaugural speech, scientific papers, and articles; Jurnals published by departments or units in ITB;Expert Directory, compiled according to the subjects of the experts; Patent, categorized according to the subjects, such as medicine, food, and software; Books, at the beginning books were not covered in this digital library, but it is the fact that many ITB faculty members publish their books related to the course materials.